Iron Supplementation Benefits Physical Performance in Women of Reproductive Age: A Systematic Review and Meta-Analysis. Issue 6 (9th April 2014) - Pasricha, Sant-Rayn; Low, Michael; Thompson, Jane; Farrell, Ann; De-Regil, Luz-Maria
Abstract: Animal and human observational studies suggest that iron deficiency impairs physical exercise performance, but findings from randomized trials on the effects of iron are equivocal. Iron deficiency and anemia are especially common in women of reproductive age (WRA). Clear evidence of benefit from iron supplementation would inform clinical and public health guidelines. Therefore, we performed a systematic review and meta-analysis to determine the effect of iron supplementation compared with control on exercise performance in WRA. We searched the Cochrane Central Register of Clinical Trials, MEDLINE, Scopus (comprising Embase and MEDLINE), WHO regional databases, and other sources in July 2013. Randomized controlled trials that measured exercise outcomes in WRA randomized to daily oral iron supplementation vs. control were eligible. Random-effects meta-analysis was used to calculate mean differences (MDs) and standardized MDs (SMDs). Risk of bias was assessed using the Cochrane risk-of-bias tool. Of 6757 titles screened, 24 eligible studies were identified, 22 of which contained extractable data. Only 3 studies were at overall low risk of bias. Iron supplementation improved both maximal exercise performance, demonstrated by an increase in maximal oxygen consumption (VO2 ? max) [for relative VO2 ? max, MD: 2.35 mL/(kg ⋅ min); 95% CI: 0.82, 3.88; P = 0.003, 18 studies; for absolute VO2 ? max, MD: 0.11 L/min; 95% CI: 0.03, 0.20; P = 0.01, 9 studies; for overall VO2 ? max, SMD: 0.37; 95% CI: 0.11, 0.62; P = 0.005, 20 studies], and submaximal exercise performance, demonstrated by a lower heart rate (MD: −4.05 beats per minute; 95% CI: −7.25, −0.85; P = 0.01, 6 studies) and proportion of VO2 ? max (MD: −2.68%; 95% CI: −4.94, −0.41; P = 0.02, 6 studies) required to achieve defined workloads. Daily iron supplementation significantly improves maximal and submaximal exercise performance in WRA, providing a rationale to prevent and treat iron deficiency in this group. This trial was registered with PROSPERO (http://www.crd.york.ac.uk/PROSPERO/prospero.asp ) as CRD42013005166.